2022
DOI: 10.3390/healthcare10081386
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography and Optical Coherence Tomography with Angiography in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory and neurodegenerative, potentially disabling disease of the central nervous system. OCT (Optical Coherence Tomography) and OCT-A (Optical Coherence Tomography with Angiography) are imaging techniques for the retina and choroid that are used in the diagnosis and monitoring of ophthalmological conditions. Their use has recently expanded the study of several autoimmune disorders, including MS. Although their application in MS remains unclear, the results seem promising. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Changes to vascularity in these areas of the retina may be better measured by OCT angiography (OCT-A), which has in recent years offered researchers the ability to non-invasively visualise the retinal microvasculature. Multiple studies have subsequently reported a reduced vascular density for patients with MS when compared to healthy www.nature.com/scientificreports/ controls in the peripapillary and/or macular regions of the retina [42][43][44] . OCT-A has also shown the potential to visualise pathological changes to the retinal anatomy earlier in the MS disease course than OCT alone 42,45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes to vascularity in these areas of the retina may be better measured by OCT angiography (OCT-A), which has in recent years offered researchers the ability to non-invasively visualise the retinal microvasculature. Multiple studies have subsequently reported a reduced vascular density for patients with MS when compared to healthy www.nature.com/scientificreports/ controls in the peripapillary and/or macular regions of the retina [42][43][44] . OCT-A has also shown the potential to visualise pathological changes to the retinal anatomy earlier in the MS disease course than OCT alone 42,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have subsequently reported a reduced vascular density for patients with MS when compared to healthy www.nature.com/scientificreports/ controls in the peripapillary and/or macular regions of the retina [42][43][44] . OCT-A has also shown the potential to visualise pathological changes to the retinal anatomy earlier in the MS disease course than OCT alone 42,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Even before clinical findings and retinopathy develop, OCT-A can be used for the evaluation of retinal microvasculature and as a screening imaging technique to detect early vascular changes as well as disease progression in children with inflammatory diseases with eye involvement. [14][15][16][17][18] Retinal and choroidal involvement have been documented in COVID-19 pediatric patients but there is not enough information about MIS-C in the literature. This study investigated vascular and perfusional changes in the retina and choroid of children with MIS-C using the OCT-A device.…”
Section: O R I G I N a L A R T I C L E Evaluation Of Vascular And Per...mentioning
confidence: 99%
“…In recent years, numerous studies demonstrated that OCT‐A has a key place in assessing early microvascular changes in children with eye problems due to inflammatory diseases such as Type 1 DM, Vogt–Koyanagi–Harada disease, glaucoma, uveitis, multiple sclerosis, and chronic renal diseases. Even before clinical findings and retinopathy develop, OCT‐A can be used for the evaluation of retinal microvasculature and as a screening imaging technique to detect early vascular changes as well as disease progression in children with inflammatory diseases with eye involvement 14–18 …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the ganglion cell layer (GCL), the inner plexiform layer (IPL), and the retinal nerve fiber layer (RNFL) are related to the overall volume of the brain's grey and white matter [ 8 ]. In recent years, OCT has been widely studied in neurodegenerative diseases such as multiple sclerosis [ 9 ], Alzheimer's [ 10 ], and Parkinson's disease [ 11 ], and RNFL thinning has been associated with neurodegeneration, disease severity, and low functionality [ 12 ]. In addition, changes in GCL, IPL, RNFL, and choroidal thickness have been investigated in psychiatric disorders [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%